Preparation of An scFv-Based Immunoliposome Specific towards Transferrin Receptor - Kusharyoto, Wien; Handayani, Ira; Sari, Martha; Fuad, Asrul Muhamad (BRIN, 2014)
An ideal therapeutic for cancer would be one that selectively targets to tumor cells, is nontoxic to normal cells, and that could be systemically delivered, thereby reaching metastases as well as primary tumor. Immunoliposomes directed by monoclonal antibody or its fragments are promising vehicles for tumor targeted drug delivery. Transferrin receptors (TfR) levels are elevated in various types of cancer cells and considered to correlate with the aggressive or proliferative ability of tumor cells. Therefore, TfR levels can be elaborated as a prognostic tumor marker, and TfR is a potential target for drug delivery in the therapy of malignant cells. Here, we report the preparation of an anti-TfR single-chain antibody variable (scFv) immunoliposome for tumor targeted delivery vehicle. The cDNA encoding the variable heavy and light chain domains of the anti-TfRscFv antibody fragment was derived from the murine monoclonal antibody Clone E6, which is specific towards transferrin receptor. The gene encoding the anti-TfR scFv fragment was codon optimized for expression in Escherichia coli, subsequently synthesized, and cloned into the expression vector pJexpress404. The His6-tagged anti-TfR scFv fragment was expressed in E. coli and purified by means of immobilized metal-ion affinity chromatography on TALON™ matrix. SDS-PAGE revealed that the scFv fragment had the size of approximately 27 kDa, which corresponded with the predicted size of the protein based on its amino acid sequence. Liposome containing 5% MPB-DOPE were prepared by ethanol injection method. Afterwards, the anti-TfR scFv fragments were covalently conjugated to the liposome to produce the anti-TfR scFv immunoliposome with the size of around 200 to 300 nm.